Escolarização, pobreza e socialização na infância e na juventude: uma proposta de plataforma de pesquisa interdisciplinar para a educação - Marcos Cezar de Freitas; Ana Paula Ferreira da Silva (EccoS – Revista Científica)
This paper presents, as a proposal, discussing a field where sociology, anthropology and ethnography are together the field research. As a result this paper is proposing to use sociological and anthropological concepts from William Corsaro, Jesús Martín-Barbero, Norbert Elias and Erving Goffman in order to elaborate a research frame about childhood and youth experience on living under poverty situation